Transformasi Pengelolaan Pendidikan Sekolah Dasar: Menghadapi Tantangan Globalisasi dan Teknologi - Putri, Ajeng Adistya; Tsania, Aura Rizky; Sundari, Marisa Ayu; Hermayanti, Risa Aulia; Handayani, Shinta Risma; Prihantini, Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The transformation of primary education has become a critical issue in the era of globalization and technological advancement. Primary education not only plays a role in shaping children’s character but also prepares them to face global challenges. This study employs a literature study method, utilizing secondary data such as research findings, books, journals, articles, and other relevant sources to analyze the impact of globalization and technology on primary education management in Indonesia. The findings highlight the importance of adapting a globally oriented curriculum, integrating technology, and strengthening character education to develop adaptive and culturally rooted generations. Challenges such as digital inequality and inadequate teacher readiness require collaboration among governments, educational institutions, private sectors, and international communities to establish an inclusive and sustainable education ecosystem